Doping prevalence and attitudes towards doping in Dutch elite sports - Balk, L.; Dopheide, M.; Cruyff, M.; Erik, D.; de Hon, O. (Scientific Journal of Sport and Performance, 2023)
The use of performance enhancing substances among elite athletes is a well-known phenomenon, but data on prevalence are inconsistent. The aim of this study was to investigate (1) the prevalence of doping use in Dutch elite athletes and (2) the attitude of elite athletes with regard to the use of performance enhancing substances. A total of 272 elite athletes completed an online questionnaire about doping use using the randomised response method and about their attitude towards the use of performance enhancing substances. The estimated prevalence of the use of doping among Dutch elite athletes during the last 12 months was 12.5 percent (95% CI 3.0 to 24.7%). The prevalence for using non-prohibited medication (without medical necessity) during the last 12 months was 15.4% (95% CI 7.1 to 23.7%). One in four athletes (23%) accepts the use of medication on prescription without a medical necessity, in order to enhance their performance. Doping prevalence among Dutch elite athletes is estimated at 12.5%, with a confidence interval from 3 to 25%. Acceptance of other performance enhancing substances is relatively high demonstrating that educational and preventive programs are essential in the fight against doping and the protection of athletes.